Migration inflow and the school performance of incumbent students - Demid Getik; Anna Sjögren; Anton Sundberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
We examine how exposure to recent migrants affects the academic performance of Swedish students. To identify the effect, we exploit variation in exposure to recent migrants between grades in a given school and year, between siblings and over time for the same individuals. We find a positive effect on native students in schools with high levels of exposure and in rural areas. At the same time, the effect is negative in large cities. Analyses of mechanisms suggest that school responses to reduce class size play a role in generating net positive effects of migrant exposure. Findings are similar when considering the more acute exposure of the 2015-2016 refugee crisis.
Keywords: I21; I24; J15; 330; schooling; peers; migration